Qualitative Study of Multilevel Barriers and Facilitators Associated With Physical Activity and Diet Among Long-haul Truck Drivers - Noe C. Crespo; Daniel Manzo; Vanessa Perez; Eric R. Walsh-Buhi; Jerel P. Calzo (Elsevier, 2024)
Background: Long-haul truck drivers (LHTD) experience disproportionately greater chronic disease risk, which may be influenced by both occupational and lifestyle factors. This study aimed to explore the multilevel factors associated with LHTD's diet and physical activity (PA). Methods: Thirty in-depth interviews were conducted with LHTD in the Southern California border region. Interview questions captured occupational and lifestyle factors relating to PA and diet at multiple levels and were analyzed using thematic analysis. Results: Emergent themes relating to both diet and PA included time constraints, attitudes and perceived beliefs, and accessibility of environments to engage in PA and healthy eating. Themes specific to PA were weather conditions and flatbed job duties. Themes specific to diet included access to refrigerators/microwaves and social interactions. Conclusion: Findings from this study can inform the development of tailored, multi-level interventions to encourage PA and healthy dietary behaviors among LHTD.